Soybean Seeds (Glycine max L.) Extract Against Cytokine Storm in ARDS Rat Model through Inhibiting Inflammation Marker - Didik Priyandoko; Wahyu Widowati; Ervi Afifah; Ika Adhani Sholihah; Cintani Dewi Wahyuni; Cahyaning Riski Wijayanti; Rizal Rizal (HAYATI Journal of Biosciences, 2023)
Several studies have suggested that "cytokine storms" are significant causes of the severity of COVID-19. Controlling and inhibiting the cytokine storm in COVID-19 could prevent the spread of COVID-19 and saves patient lives. Soybean (Glycine max L.) is known to have various biological activities. This study aims to examine bioactive compounds in SSE and the effect of SSE on the ARDS rats model. A total of 25 Sprague Dawley Lipopolysaccharide-induced rats were used. Determination of serum IL-1β, IL-12, and lung TNF-α levels was performed by ELISA method. NF-κB and IFN-γ expression were determined by the qRTPCR method. IL-6 expressions were analyzed by immunohistochemistry assay. The bleeding, inflammation, and alveolus collapse score were analyzed using the HE staining method. The results showed that SSE could decrease the level of IL-1β, IL-12, TNF-α, IL-6, NF-kB, and IFN-γ and improve the bleeding, inflammation, and alveolus score in the lung. SSE could decrease the pro-inflammatory cytokines and improve lung condition in ARDS rats model.